FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN AIR SUSU IBU PADA IBU POST SECTIO CAESARIA DI RSUD. DR. PIRNGADI KOTA MEDAN TAHUN 2015 - Yusrina Mangunsong (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2016)
On delivery to the action sectio Caesaria that worried the mother is the inability of mothers in breastfeeding their babies for 68% of the mother post sectio caesarea experiencing difficulties with infant care, moving up and down on the bed and set a comfortable position during breastfeeding due to pain, thus causing patients delaying breastfeeding since the beginning of the baby, because the discomfort during breast feeding lasts or the increased intensity of pain after surgery. This study aims to determine Factors associated with the provision of mother's milk in the mother post Sectio Caesaria in Hospital Dr. Pirngadi Medan in 2015. This type of research is descriptive analytic research with cross sectional approach, the population in this study were all women giving birth to the action sectio Caesaria selected consecutiv sampling with a total of 112 respondents. The result is hajil Chi square test showed that factors related to knowledge, surgical wound pain, motivaasi, anxiety, support the husband / family and support of health workers, while not related, administration of drugs for hormone prolactin meninggatkan with P value <0.05. Results of multivariate analysis with logistic regression showed that there is a relationship together and knowledge is most associated with breastfeeding post SC with a P value of 0.032 <0.05. The OR value obtained is 0.026. It can be concluded that not all hypotheses can be accepted. Health services and health workers need to provide health education and promotion of lactation in particular of the factors associated with breastfeeding, it can be given at the time of antenatalcare.